Analisis Dampak Kebijakan Fiskal terhadap Pertumbuhan Ekonomi di Indonesia - Nawawi, Ahmad; Irawan, Ferry (Jurnal Ekonomi dan Pembangunan Indonesia, 2010)
This paper presents an analysis of the effect of fiscal policy in Indonesia based on a VAR ap proach. Fiscal policy shocks are identified as a structural residuals related to unexpected government expenditures and tax revenues. Impulse responses are then used to simulate the dynamic response of key macroeconomics variables of shocks. The analysis shows that GDP responses negatively to tax shocks, and positively to expenditure shock. Moreover, disposable income and private consumption react negatively to taxation and positively to government expenditures. Altogether the results are consistent with that of Keynesian models.